Implication of the Whitefly Bemisia tabaci Cyclophilin B Protein in the Transmission of Tomato yellow leaf curl virus - Kanakala, Surapathrudu; Ghanim, Murad (Frontiers in Plant Science, 2016)
Tomato yellow leaf curl virus (TYLCV) is a single-stranded (ssDNA) begomoviruses that causes severe damage to tomato and several other crops worldwide. TYLCV is exclusively transmitted by the sweetpotato whitefly, Bemisia tabaci in a persistent circulative and propagative manner. Previous studies have shown that the transmission, retention and circulation of TYLCV in its vector involves interaction with insect and endosymbiont proteins, which aid in the transmission of the virus, or have a protective role in response to the presence of the virus in the insect body. However, only a low number of such proteins have been identified. Here, the role of B. tabaci Cyclophilin B (CypB) in the transmission of TYLCV protein was investigated. Cyclophilins (Cyps) are a large family of cellular prolyl isomerases that have many molecular roles including facilitating protein-protein interactions in the cell. One cyclophilin protein has been implicated in aphid-luteovirus interactions. We demonstrate that the expression of CypB from B. tabaci is altered upon TYLCV acquisition and retention. Further experiments used immunocapture-PCR and co-immunolocalization and demonstrated a specific interaction and colocalization between CypB and TYLCV in the the midgut, eggs and salivary glands. Membrane feeding of anti-CypB antibodies and TYLCV infected plants showed a decrease in TYLCV transmission, suggesting a critical role that CypB plays in TYLCV transmission. Further experiments, which used membrane feeding with the CypB inhibitor Cyclosporin A (CsA) showed decrease in CypB-TYLCV colocalization in the midgut and virus transmission. Altogether, our results indicate that CypB plays an important role in TYLCV transmission by B. tabaci.